1991
DOI: 10.1111/j.1747-6593.1991.tb00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in Surface Waters and Groundwaters

Abstract: Diffuse pollution by pesticides, particularly herbicides, has been recognized in the UK for several years. Atrazine, Simazine, Mecoprop, Dimethoate and, more recently, Isoproturon and Chlortoluron have been found frequently in surface waters at concentrations up to 0.5 &1, with a maximum of 11.5 pg/l. Pesticides are detected less frequently in groundwaters, at concentrations generally lower than 0.1 pg/l. Atrazine is found most frequently. Concentrations in untreated surface and groundwaters have generally bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 4 publications
0
21
0
2
Order By: Relevance
“…Atrazines removal from the Irish market in 2007 coincided with the commencement of this monitoring program. Atrazine has been frequently detected in other European groundwater studies (Batista et al 2002;Cerejeira et al 2003;Croll 1991;Gonçalves et al 2007;Loos et al 2010). Most other monitoring programs analyze for atrazine's transformation products which tend to be found more frequently than the parent compound and often in absence of the parent compound (Gonçalves et al 2007;Spliid and Køppen 1998).…”
Section: Frequency Of Pesticidesmentioning
confidence: 98%
“…Atrazines removal from the Irish market in 2007 coincided with the commencement of this monitoring program. Atrazine has been frequently detected in other European groundwater studies (Batista et al 2002;Cerejeira et al 2003;Croll 1991;Gonçalves et al 2007;Loos et al 2010). Most other monitoring programs analyze for atrazine's transformation products which tend to be found more frequently than the parent compound and often in absence of the parent compound (Gonçalves et al 2007;Spliid and Køppen 1998).…”
Section: Frequency Of Pesticidesmentioning
confidence: 98%
“…, with a maximum of 11·5 g l −1 (Croll, 1991). Being highly soluble and persistent, atrazine (Anon, 1992b,c;Ivens, 1995;Steele, 1995; is the pesticide most frequently exceeding the 0·1 g l −1 limit in water.…”
Section:   mentioning
confidence: 98%
“…The pesticide monitoring program started by Anglian Water in 1985 (Croll, 1991) has included rivers, reservoirs and groundwaters. With the exception of the triazines (atrazine and simazine), the pesticides detected are those used in the greatest tonnages in U.K. agriculture.…”
Section:   mentioning
confidence: 99%
“…Atrazine concentrations can exceed the general quality standard for surface and drinking water (5 µg l −1 ) (Giroux, 2015). Values ranging from 9 to 25 µg l −1 in Europe (Croll, 1991;Legrand et al, 1991), 87 to 100 µg l −1 in North America (Steinheimer, 1993;Graymore et al, 2001), and up to 150 µg l −1 in Australia (Graymore et al, 2001) have been reported. Although it has been proposed an acute toxicity threshold value of 20 µg atrazine l −1 , (Diana et al, 2000), under concentrations lower than 20 µg l −1 , atrazine was reported to cause sub-lethal effects in various aquatic organisms such as unicellular algae (DeLorenzo et al, 2001).…”
Section: Case Of Psii Inhibitors and Temperaturementioning
confidence: 99%